2013
DOI: 10.1016/j.molmed.2012.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen synthesis and signaling pathways during aging: from periphery to brain

Abstract: Estrogens are the primary female sex hormones and play important roles in both reproductive and non-reproductive systems. Estrogens can be synthesized in non-reproductive tissue as liver, heart, muscle, bone and brain. The tissue-specific estrogen synthesis is consistent with a diversity of estrogen actions. Here, we will focus on tissue and cell-specific estrogen synthesis and estrogen receptor signaling. This review will include three parts: (I) tissue and cell-specific estrogen synthesis and metabolism, (II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
444
0
18

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 617 publications
(469 citation statements)
references
References 164 publications
(185 reference statements)
7
444
0
18
Order By: Relevance
“…Evidence has also shown that ERα and ERβ activate different signal transduction pathways, especially the MAPK system, which is usually determined by intracellular protein phosphorylation or calcium increase [49,50]. We found that after CFA application, expression of ERK in SCDH from OVX rats was significantly higher than that of controls, which was reversed by estrogen replacement.…”
Section: Functions Of Erk In the Modulation Of Estrogen In Inflammatomentioning
confidence: 63%
“…Evidence has also shown that ERα and ERβ activate different signal transduction pathways, especially the MAPK system, which is usually determined by intracellular protein phosphorylation or calcium increase [49,50]. We found that after CFA application, expression of ERK in SCDH from OVX rats was significantly higher than that of controls, which was reversed by estrogen replacement.…”
Section: Functions Of Erk In the Modulation Of Estrogen In Inflammatomentioning
confidence: 63%
“…Az extragonadális ösztrogének szintézise emellett szövetenként eltérő és összetett reguláció alatt áll [14]. Közvetlen adatok igazolják, hogy menarche előtt és a posztmenopauza idején is folyamatos és jelentős ösztrogéntermelés zajlik a zsírszövetben, az emlő-ben, a vesében és a bőrben [15]. Az ösztrogénhatást közvetítő ERα és ERβ ösztrogénreceptorok jelenlétét kimutatták számos perifériás szervben; az ERα-t a csontban és a májban, míg az ERβ-t a vastagbélben, a csontvelőben, a vascularis endothelben, a tüdőben, a hólyagban és az agyban [15].…”
Section: öSszefoglaló Közleményunclassified
“…Közvetlen adatok igazolják, hogy menarche előtt és a posztmenopauza idején is folyamatos és jelentős ösztrogéntermelés zajlik a zsírszövetben, az emlő-ben, a vesében és a bőrben [15]. Az ösztrogénhatást közvetítő ERα és ERβ ösztrogénreceptorok jelenlétét kimutatták számos perifériás szervben; az ERα-t a csontban és a májban, míg az ERβ-t a vastagbélben, a csontvelőben, a vascularis endothelben, a tüdőben, a hólyagban és az agyban [15]. A kulcsfontosságú aromatázenzim jelenlétét az agy számos területén és az osteoblastokban is igazolták [8,16].…”
Section: öSszefoglaló Közleményunclassified
“…DHEA secreted from the zona reticularis of the adrenal glands, and stored in the blood as a reservoir as DHEAS, is the ultimate precursor. Adipose tissue is another notable source of oestrogen synthesis (Cui et al 2013). White adipose tissues (the predominant type in obesity) express significant quantities of cytochrome P450 aromatase enzyme (CYP19A1) in the abdominal adipose fat of male human samples, which is the final catalyst in the conversion of androgens to oestrogens (Wang et al 2013, Polari et al 2015.…”
Section: Oestrogen Metabolism In Adipose and Prostate Cancermentioning
confidence: 99%